2021
DOI: 10.1021/acs.jmedchem.1c00693
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Properties of a Benzimidazole Benzylpyrazole Lysine Demethylase Inhibitor: Mechanism-of-Action, Binding Site Analysis, and Activity in Cellular Models of Prostate Cancer

Abstract: Jumonji domain-containing lysine demethylase (KDM) enzymes are encoded by genes of the KDM superfamily. Activities of the KDM4 subfamily promote aggressive phenotypes associated with prostate cancer (PCa). Previously, we discovered a benzimidazole pyrazole molecule that inhibited KDM4 isoforms with properties tractable for development. Here, we demonstrate that a benzyl-substituted variant of this inhibitor exhibits improved potency in biochemical assays, is cell-permeable, and kills PCa cells at low micromola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In a subsequent study, structure optimization resulted in compound 24b with 10-fold increased potency (KDM4E IC 50 = 0.9 μM in FDH-based assay). 24b exhibited cytotoxicity against prostate cancer cell lines (GI 50 = 8 μM for LnCap and DU145 cell lines) and a nondisease control cell line (GI 50 = 26 μM, human prostate epithelial cells) . A kinetics-based study revealed that compound 24b is not competitive with the 2-OG cosubstrate.…”
Section: Kdm4 Inhibitorsmentioning
confidence: 98%
See 1 more Smart Citation
“…In a subsequent study, structure optimization resulted in compound 24b with 10-fold increased potency (KDM4E IC 50 = 0.9 μM in FDH-based assay). 24b exhibited cytotoxicity against prostate cancer cell lines (GI 50 = 8 μM for LnCap and DU145 cell lines) and a nondisease control cell line (GI 50 = 26 μM, human prostate epithelial cells) . A kinetics-based study revealed that compound 24b is not competitive with the 2-OG cosubstrate.…”
Section: Kdm4 Inhibitorsmentioning
confidence: 98%
“…As KDM4s are 2-oxoglutarate (2-OG) dependent dioxygenases, most of the small molecule inhibitors are 2-OG analogs and their derivatives that chelate the Fe 2+ in the catalytic binding pocket, thereby suppressing KDM4 activity. However, most of these inhibitors are lacking selectivity and/or cell permeability. Peptide-like inhibitors were also developed by mimicking the KDM4 substrate H3K9me3/K36me3 peptides and showed non-2-OG competitive properties. Some natural products metabolites of bacteria and plants have been identified as KDM4 inhibitors.…”
Section: Kdm4 Inhibitorsmentioning
confidence: 99%
“…The benzimidazole-pyrazole hybrids possessed potential anticancer activity, [41][42][43][44][45] and among them, hybrid 15 (IC 50 : 4.3 µM, SRB assay) was 3.6-fold more potent than etoposide (IC 50 : 15.6 µM) against HCT-116 cells. [45] Mechanistically, hybrid 15 could induce apoptosis and arrest cell cycle at G0/G1 phase.…”
Section: Benzimidazole-sulfone/ Sulfonamide Hybridsmentioning
confidence: 99%
“…These chromatin regulatory enzymes are being considered as therapeutic targets for small molecule inhibition in several cancers, 81 including prostate cancer. 82,83 Thus, small molecule inhibitors targeting individual BET bromodomain proteins, in combination with inhibitors of other chromatin regulators, represent an innovative approach to solve the problem of emerging ADT-resistant forms of prostate cancer.…”
Section: Chromatin Regulators In Mechanisms Of Emt and Chemoresistancementioning
confidence: 99%
“…The genomic instability that emerges and propagates during the expansion of malignant clonal prostate cancer cells likely creates a fertile environment for genetic disruption of these chromatin regulators. These chromatin regulatory enzymes are being considered as therapeutic targets for small molecule inhibition in several cancers, 81 including prostate cancer 82,83 . Thus, small molecule inhibitors targeting individual BET bromodomain proteins, in combination with inhibitors of other chromatin regulators, represent an innovative approach to solve the problem of emerging ADT‐resistant forms of prostate cancer.…”
Section: Bet Proteinsmentioning
confidence: 99%